Genetics : from genes to genomes - Hartwell, Leland (New York : McGraw-Hill Education, 2018)
Genetics: From Genes to Genomes is a cutting-edge, introductory genetics text authored by an unparalleled author team, including Nobel Prize winner, Leland Hartwell. This edition continues to build upon the integration of Mendelian and molecular principles, providing students with the links between the early understanding of genetics and the new molecular discoveries that have changed the way the field of genetics is viewed.
Part I Basic Principles: How Traits Are Transmitted -- Part II What Genes Are and What They Do -- Part III Analysis of Genetic Information -- Part IV How Genes Travel on Chromosomes -- Part V How Genes Are Regulated -- Part VI Using Genetics -- Part VII Beyond the Individual Gene and Genome.
Includes index.
Keywords: Genetics